WAYS TO OPTIMIZE COSTS AND PRODUCT COST IN MANUFACTURING ENTERPRISES - Nematjonova Risolatxon Dilshodbek qizi (TADQIQOTLAR, 2026)
Abstract This article examines the classification of production costs, the mechanisms of product cost formation, and modern methods for their optimization in manufacturing enterprises. In the context of a market economy, the issues of reducing product costs, using resources efficiently, and implementing modern management technologies (Lean production, Kaizen, KPI) to increase the competitiveness of enterprises are analyzed. Furthermore, cost productivity is demonstrated through practical calculations and mathematical-economic models.